Mechanism of the traumatic brain injury induced by blast wave using the energy assessment method. (March 2022) - Liu, Yuhao; Lu, Yongtao; Shao, Yang; Wu, Yanli; He, Jintao; Wu, Chengwei
Highlights: The indicator of energy was used to explore the mechanism of b-TBI. The kinetic energy and strain energy generated by the head may be the main causes of b-TBI. The capacity of the energies dissipated by the head is not sensitive to the impact direction. Abstract: Although blast-induced traumatic brain injury (b-TBI) is well recognized for its significance in the military population, the unique mechanisms of primary b-TBI remain undefined. The aim of the present study is to unveil the mechanism of the traumatic brain injury induced by the shock wave using the energy assessment method. First, the magnetic resonance images of the human head were processed to establish the finite element (FE) model of the human head including the skin, the skull, the brain and other structures. The simulation of the shock wave was implemented using the Coupled Eulerian-Lagrange (CEL) method, a fluid-solid coupling model of explosive shock wave-head. The coupled model was used to simulate the situations of head subjected to the frontal direction, the side direction and the rear direction by explosive shock wave. The predictions of the FE results were validated by comparing them with previous studies. Then, the degree of b-TBI in three different directions i.e., the frontal direction, the side direction and the rear direction, was assessed to investigate the influence of the direction of the shock wave on the b-TBI. Finally, the various energies including strain energy, kinetic energy, viscous energy and creep energy were extracted from the FE calculations for investigating the mechanism of b-TBI. The results showed that under the scenario of the shock wave, the brain injury was caused by the combined actions of acceleration of the head and the deformation of the skin& facial muscle tissues, the brain and the cerebrospinal fluid (CSF). In addition, it was also found that the dissipation capacity of the head was not sensitive to the impact direction. The present study provides important data and theoretical basis for the mechanism of b-TBI.